Socio-economic Phenomenological Study: Analysis of the Causing Factors of Poverty in Fishermen's Families in Gentung Village, Pangkep Regency - Sahrul, Sahrul; Nasrul, Nasrul; Qaiyimah, Dinil; Nasir, Nasir; Nurniah, Nurniah (Indonesian Journal of Fundamental and Applied Geography, 2026)
Coastal areas often present a welfare paradox, where abundant marine resource potential is not always directly proportional to the level of welfare of fishing communities, so that poverty remains a structural and multidimensional issue. This study aims to analyze the meaning of poverty in the lived experiences of fishing families and identify the social and economic factors that shape their vulnerability. The study used qualitative methods with a phenomenological approach to explore the awareness, perceptions, and survival strategies of fishing families in the face of economic uncertainty. The study was conducted in Gentung Village, Pangkajene and Kepulauan Regency, with data collection techniques using in-depth interviews, observation, and documentation. The results show that fishermen's poverty is influenced by low levels of education, strong patron-client relationships, and cultural constructs that interpret risk as part of destiny, which indirectly limit social mobility and economic innovation. Economically, income fluctuations due to seasonal dependence, limited access to formal financial institutions, and high-interest informal lending practices reinforce the cycle of debt and household vulnerability. This study recommends strengthening educational and financial literacy, developing more inclusive community-based economic institutions, and contextual and participatory business diversification strategies to encourage social transformation and improve fishermen's welfare sustainably.